2016
DOI: 10.1159/000445203
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum Bisphenol A Levels in Diabetic Hemodialysis Patients

Abstract: Background: Bisphenol A (BPA) has been implicated as an ‘endocrine disruptor'. We aimed at exploring the association between serum BPA levels and patient characteristics, particularly the presence of diabetes mellitus, and laboratory parameters in hemodialysis patients. Methods: This study included 47 chronic hemodialysis patients. Patient characteristics were recorded. Blood was drawn before and after hemodialysis session. Serum BPA levels were measured by the high-performance-liquid-chromatography and labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…2018). Likewise, BPA concentrations were increased after a single hemodialysis session in patients with diabetes (Turgut et al. 2016) or uremia (Shintani 2001), and urinary BPA levels were significantly higher in patients using BPA-free dialyzers in comparison with BPA-containing dialyzers (Bosch-Panadero et al.…”
Section: Discussionmentioning
confidence: 99%
“…2018). Likewise, BPA concentrations were increased after a single hemodialysis session in patients with diabetes (Turgut et al. 2016) or uremia (Shintani 2001), and urinary BPA levels were significantly higher in patients using BPA-free dialyzers in comparison with BPA-containing dialyzers (Bosch-Panadero et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in ESRD patients, decline in kidney function leads to the accumulation of BPA, yielding higher blood levels [28,30]. Moreover, during dialysis, the contact of blood with polymeric medical devices, such as dialyzers made of polycarbonate, polysulfone, or polyester, may expose ESRD patients to BPA [23,28,30,36]. In addition to dialyzers, BPA present in dialysate fluid is a source of exposure [23].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, detectable amounts of BPA were reported to leach from hemodialyzers (Haishima et al 2001;Murakami et al 2007), and plasma BPA levels were lower in hemodialysis patients using polynephron (BPA-free) versus conventional polysulfone dialyzer membranes (Mas et al 2018). Likewise, BPA concentrations were increased after a single hemodialysis session in patients with diabetes (Turgut et al 2016) 2001), and urinary BPA levels were significantly higher in patients using BPA-free dialyzers in comparison with BPAcontaining dialyzers (Bosch-Panadero et al 2016). Similar studies have reported increased serum DEHP levels in hemodialysis patients (Wahl et al 2004).…”
Section: Discussionmentioning
confidence: 99%